Chapter The colour of Valencian silk fabrics in the European market (1475-1513) - Navarro Espinach, Germán (Datini Studies in Economic History, 2022)
Our research compares guild ordinances, judicial proceedings, technical manuals of dyeing and especially fiscal sources in the Valencian archives to check the fashion trends on the colour of silks fabrics during the 15th-16th centuries in relation to what was happening in the European market at that time. The silk declarations in Valencia city from 1475 to 1513 makes it possible to establish a database of 3,871 fiscal registers with more than 90,000 meters of Valencian textiles (100,220 varas or alnes). The 73.47 percent of them was in black. This colour was also fashionable in the silk industry of Genoa, from where there was an important technological transfer to Valencia through the immigration of technical masters, workers and specialized businessmen.